Hydrogeological Conceptual Model in the Middle of Randublatung Groundwater Basin. Issue 1 (November 2021) - Setyaningsih, D L; Setyawan, K D; Putra, D P E; Salahuddin,
Abstract: Randublatung groundwater basin is one of the groundwaters basins with massive utilization of groundwater pumping. However, the knowledge of the comprehensive hydrogeological system in this groundwater basin is limited, so this research aims to determine a comprehensive hydrogeological conceptual model of the Randublatung groundwater basin. The methodology was conducted by collecting secondary and primary data of deep and shallow wells to evaluate boundaries of pattern and direction of groundwater flow and develop the aquifer system's geometry. The result shows that the groundwater flow boundaries are Grogol River in the west, Wado River in the East, Bengawan Solo river in the South as a river boundary, and Rembang Mountains in the North as a constant head boundary. Therefore, groundwater flows from the hills area to the Bengawan Solo River and the north as the river's flow. Based on the log bor evaluation, the aquifer system of the study area consist of an unconfined aquifer with a maximum thickness of 20 m and three layers of confined aquifers with thickness vary between 8 to 60 m. the hydraulic conductivity of the aquifers depends on the aquifer's lithology range from sand, gravel, limestone, and sandstone. This hydrogeological conceptual model provides essential information for numerical groundwater models in the middle of the Randublatung groundwater basin.